Penerapan Prinsip Transparansi dan Akuntabilitas dalam Pengelolaan Dana Infaq (di TPQ Al-Khuriyah Bangil -Pasuruan) - Lailatul Azizah (Akuntansi: Jurnal Akuntansi Integratif, 2022)
The development and quality improvement of Madin and TPQ in Pasuruan, through the WAKMUQIDIN program (wayahe gather to build TPQ lan Madin). Madin and TPQ not only continue to support learning Islamic religious education in formal schools. However, being at the forefront in the formation of morals and character for students. This research is a descriptive study with a qualitative approach, the researcher will describe the state of the field with the aim of finding a strategy regarding the management of infaq funds, starting from the planning, organizing, monitoring, and controlling processes. From the results of the data analysis, it can be seen that “the financial staff lacks insight regarding the administration of the institution, especially in terms of bookkeeping so that financial data is not organized and makes it difficult to evaluate monthly or annual financial reports”. The management system for managing infaq or financial funds is like an engine romm at an educational management institution and can affect every teaching and learning activity if it is not responded to properly and the steps that need to be taken are to provide guidance to financial on managerial and structured infaq funds.